The school of the sea and education in times of social isolation (Palíndromo, 2021)
The paper narrates how the Escuela del Mar, Mar del Plata, Argentina, copes with social isolation, based on virtual interviews and the review of materials, audios and videos shared by teachers, parents and students. The conclusion is that artistic activities act as a link between the external and internal world.
Keywords: Alternative education.; Artistic activities.; Social isolation.